The Hate U Give Guide - Kansas State University, K-State First (My University, 2018)
This guide provides resources for faculty and staff at Kansas State University on the book "The Hate U Give" by Angie Thomas. Included in the guide are discussion questions, suggested classroom activities, other titles of interest, vocabulary, and additional resources.
Citation: K-State First (2018). The Hate U Give Guide [Brochure]. Manhattan, Kansas: K-State First.
Keywords: Hate U Give, The; Common reading program; Guide; First-year experience program; Application of learning